2017
DOI: 10.17925/ohr.2017.13.01.21
|View full text |Cite
|
Sign up to set email alerts
|

Can We Improve Thyroid Fine-needle Aspiration Cytology Adequacy in a Low-volume Thyroid Center?

Abstract: I ntroduction: Thyroid cancer is the most common endocrine malignancy, and has shown an increase in incidence in recent decades. Fine-needle aspiration cytology (FNAC) is the mainstay of assessment of thyroid nodules and diagnosis of malignancy. Several reports have suggested that ultrasound (US)-guided FNAC has many advantages over palpation-guided biopsy. . Also, time to diagnostic FNAC was significantly shorter in the SUS-FNAC group: 24.2 ± 4.5 versus 54.9 ± 11.4 days (p=0.01, unpaired t-test). Conclusion: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…While the use of ultrasound for guided FNA has already increased the diagnostic accuracy in general [15], implementation of ROSE has the capacity to additionally improve the diagnostic yield with less necessity for repeat FNA. In 1992, Eisele et al [16] observed that an immediate cytopathological procurement and evaluation of specimen led to a significant reduction of unsatisfactory results in head and neck masses.…”
Section: Discussionmentioning
confidence: 99%
“…While the use of ultrasound for guided FNA has already increased the diagnostic accuracy in general [15], implementation of ROSE has the capacity to additionally improve the diagnostic yield with less necessity for repeat FNA. In 1992, Eisele et al [16] observed that an immediate cytopathological procurement and evaluation of specimen led to a significant reduction of unsatisfactory results in head and neck masses.…”
Section: Discussionmentioning
confidence: 99%